Financial systems integration in East-Asia: the uncovered interest parity condition - Hassan, Ibrahim Bakari; Mohamed, Azali; Lee, Chin (2014)
The paper investigates financial system integration in selected East-Asian countries (ASEAN5+3) under the Uncovered Interest Parity (UIP) hypothesis. The global vector autoregressive Model (GVAR) is used on the quarterly data of interest rate, exchange rate; real outputs, prices and equity prices over the period of 1979Q2 to 2011Q4 for 33 countries. Contemporaneous effect of foreign variables on domestic counterparts is estimated to identify the level of linkages across the variables. The result shows high linkages in equity prices and real output than on short-term interest rate and inflation rate. On the UIP, restrictions are imposed on the generated cointegration vectors based on the respective long-run theories. The result does not support the holding of UIP and by implication; no financial system integration in the ASEAN5+3 countries, thus restriction to capital mobility is still high. Although the analysis does not consider the sensitivity of the term-structure of the interest rate (as only the short-term interest rate is observed), it is advisable for further research to consider long-term interest rate. It is also recommended for the respective policymakers to observe the way their short-term interest rate are related.